2000
DOI: 10.2172/754949
|View full text |Cite
|
Sign up to set email alerts
|

Mixing of process heels, process solutions, and recycle streams: Results of the small-scale radioactive tests

Abstract: The contact time was extended to 1 week to ensure equilibrium was attained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Since the turbidity values of the mixtures were appreciably greater than the controls, new precipitates must have formed. In support of this observation, Lumetta et al (2000) reported a significant amount of precipitates formed when AN-107 was mixed with AW-101 at a ratio of 3:30, respectively.…”
Section: Envelope Mixing Experimentsmentioning
confidence: 62%
See 2 more Smart Citations
“…Since the turbidity values of the mixtures were appreciably greater than the controls, new precipitates must have formed. In support of this observation, Lumetta et al (2000) reported a significant amount of precipitates formed when AN-107 was mixed with AW-101 at a ratio of 3:30, respectively.…”
Section: Envelope Mixing Experimentsmentioning
confidence: 62%
“…These tests were conducted because no turbidity was visually observed (no turbidity meter was used in the hot cells) when active feed samples were mixed, contrary to the results from the simulant mixing study and those of Lumetta et al (2000). Initially, this inconsistency was believed to be due to differences in feed concentrations; the simulants were more concentrated than the active feed samples.…”
Section: Dilute Envelope Mixing Experimentsmentioning
confidence: 99%
See 1 more Smart Citation